Tridimenzionalno ovrednotenje oblikovnih značilnosti obraza otrok v obdobju mlečnega zobovja - Malgaj, Tine (Medicinski razgledi, 2013)
Backgrounds. The diagnosis and treatment of dentofacial deformities are based on optimal functional occlusion and especially on the facial soft tissues appearance. The aim of this study was to assess soft tissue characteristics of the face in children without malocclusion during the primary dentition phase in order to evaluate the differences between the average boy's and girl's faceš. Methods. 28 children (16 boys, 12 girls) during the primary den- tition phase, aged from 5 to 6 years (5.95 0.34), without malocclusion were included in the study. Surface fadal images using 3D laser surface scanner system were obtained and the 3D average facial template of an average boy's and girl's face was constructed. Differences between boy's and girl's fadal templates were qualitatively and quantitatively evaluated. The color deviation maps were used to qualitatively evaluate the differences between the overlapping facial template. For a quantitative evaluation the values of different parameters that described the facial surface of each subject were compared. To verify the differences in variables between the boys and girls, we used the Mann-Whitney's U-test. For the level of statistical significance a standard value of at least 95% confidence interval (p < 0.05) was determined.Results. The average boy's facial template was larger than the average girl's facial template. Two variables that described the size of the face in the lateral (left eye width) and vertical (middle fadal height) directions were significantly larger in boys (p<0.05). Conclusions.Boys had bigger faces than girls at the time of measurement.
Keywords: 3D imaging system; 3D slikovni sistem; face; obraz; primary dentition phase; obdobje mlečnega zobovja